Generic Pharmaceuticals as a Source of Diuretic Contamination in Athletes Subject to Sport Drug Testing - Eichner, Amy; Lewis, Laura A.; Leonard, Bridget; Wagoner, Ryan M. Van; Eichner, Daniel; Fedoruk, Matthew N. (Frontiers in Sports and Active Living, 2021)
This paper describes nine instances of positive anti-doping tests that could be accounted for by the use of permitted generic prescription drugs contaminated with diuretics, which are prohibited in sport at all times under the WADA Prohibited List. The contamination levels found in the medications are reported and were below FDA limits for manufacturers that are based primarily on safety considerations. These cases demonstrate that great care must be taken to identify the source of low-level anti-doping positives for diuretics reported by WADA-accredited laboratories, and possibly other prohibited substances as well, in order to avoid sanctioning innocent athletes. An evaluation of the cases in this paper supports an approach which establishes a laboratory minimum reporting level (MRL) for diuretics found most commonly in medications. A global consensus after extensive review of similar anti-doping cases has resulted in implementation of a recently announced solution regarding potential diuretic contamination cases.